Form And Process of The Inheritance of Pekalongan Batik Ornaments At Larissa Batik Kampung Batik Pesindon (Catharsis, 2021)
In general, the culture in Indonesia has existed for a long time, and it is carried out from generation to generation through the process of cultural inheritance. One of the diversity of Indonesian culture is the batik art culture that has been attached to the Indonesian people, especially the Javanese people. In the city of Pekalongan, the batik industry is growing rapidly, and the batik artworks are much in demand by the wider community. As a city located on the northern coast of Java, Pekalongan batik has experienced many cultural influences from outside, thus enriching the ornaments of Pekalongan batik itself. One of the places in Pekalongan that are already known as a village for batik artisans is Kampung Batik Pesindon. Its fame as a village for batik artisans has even been known outside Pekalongan. Kampung Batik Pesindon, which is dominated by the home batik industry, continues to survive in the midst of urban development and modernization. The existence of a batik home industry in the Kampung Batik Pesindon area has survived, and it has been passed down from generation to generation until it became the forerunner to the formation of Kampung Batik Pesindon itself. The formation of the Kampung Batik Pesindon is one of the efforts to continue to maintain the batik culture, which is closely related to the life of the people of Kampung Batik Pesindon. One of the batik industries in Kampung Batik Pesindon that still maintains the preservation of Pekalongan batik is Batik Larisa. Keywords: inheritance, ornament, Pekalongan batik, batik village